2014
DOI: 10.1021/la4045896
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Morphologies of Evaporation-Triggered Asphaltene Nanoaggregates

Abstract: We use atomic force microscopy to observe the structural changes in petroleum-asphaltene aggregates in air as a function of temperature. The aggregates are obtained by evaporating a toluene solution containing asphaltene. Increase in temperature leads to transition from self-assembled fractal structures to substantially larger mobile "liquid-like" domains that show distinct tendencies of substrate repulsion and self-coalescence. This new aggregation dynamics of asphaltene can be explained by temperature-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…A fairly linear trend up to 60°C is observed but a significant rise in the solubility parameters has been seen at temperatures above 60°C, it is presumed to occur because of a possible phase transition of asphaltenes above 60°C. This A c c e p t e d M a n u s c r i p t observation is in agreement with Mehranfar et al (2014), who demonstrated that asphaltenes transform from being purely amorphous phase at temperature below 70°C to a liquid crystalline phase above 70°C. It is also observed that average asphaltenes solubility parameter has largely remained in between 18.5 -22.5 MPa 0.5 .…”
Section: Effect Of Temperature On Asphaltenes Solubility Parametersupporting
confidence: 91%
See 1 more Smart Citation
“…A fairly linear trend up to 60°C is observed but a significant rise in the solubility parameters has been seen at temperatures above 60°C, it is presumed to occur because of a possible phase transition of asphaltenes above 60°C. This A c c e p t e d M a n u s c r i p t observation is in agreement with Mehranfar et al (2014), who demonstrated that asphaltenes transform from being purely amorphous phase at temperature below 70°C to a liquid crystalline phase above 70°C. It is also observed that average asphaltenes solubility parameter has largely remained in between 18.5 -22.5 MPa 0.5 .…”
Section: Effect Of Temperature On Asphaltenes Solubility Parametersupporting
confidence: 91%
“…Akbarzadeh et al (2005) used a generalized regular solution model for their data to estimate asphaltenes precipitation from n-alkane diluted heavy oils and bitumen. Mehranfar et al (2014) used atomic force microscopy to observe the structural changes in asphaltene nano-aggregates as a function of temperature (25 -80°C), demonstrating the transition of asphaltenes to liquid phase with increase in temperature above 70°C. Maqbool et al (2011) used optical microscopy to evaluate the effect of temperature on asphaltenes precipitation kinetics.…”
Section: Introductionmentioning
confidence: 99%
“… They found that at higher temperatures the onset time of precipitation is shorter. Mehranfar et al studied the effect of temperature (25–80 °C) on asphaltene structural changes in air using atomic force microscopy . They showed that an increase in temperature above 70 °C leads to transition from self‐assembled fractal structures to substantially larger liquid phase.…”
Section: Introductionmentioning
confidence: 99%
“…A sphaltenes are one of the most problematic and less understood compounds of crude oil which are soluble in aromatic solvents and insoluble in saturated hydrocarbons. [1][2][3][4][5] Any changes in thermodynamic conditions (pressure, temperature, or oil composition) destabilizes asphaltenes and causes a variety of problems in both the upstream and downstream oil industry. [6][7][8] Reducing the well inflow performance and increasing the overall operating cost, wettability alteration of the reservoir rock, plugging surface facilities and flow lines, contributing to catalyst deactivation, and equipment fouling are some of their detrimental consequences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation